Basic Income Advocacy in Canada: Multiple Streams, Experiments and the Road Ahead - Frankel, Sid (Political Activism and Basic Income Guarantee, 2020)
Basic income has a long history in Canada, going back to the Great Depression. Its recognition has risen and fallen cyclically, several experiments have been mounted, and some programs, such as the Canada Child Benefit and the Old Age Security demogrant, have been identified as partial basic income schemes. However, a universal basic income for all members of the Canadian political community has never been visibly close to implementation. Against this background, this chapter examines basic income political advocacy from three vantage points. First, the multiple streams framework is used to assess linkages of basic income in the problem stream, its position in the policy stream and forces at play in the political stream. Next, the fate of experiments is described, along with approaches for increasing the likelihood that experiments will result in full-scale policy implementation if outcomes are sufficiently promising. Third, some advocacy strategies for the future are recommended.